The Phoenix ballroom : a novel - Hogan, Ruth, 1961- (William Morrow, an imprint of HarperCollinsPublishers, 2024)
A wealthy widow, 74-year-old Venetia Hargreaves declares her independence, first with a makeover, then by adopting a dog and then by buying the Phoenix Ballroom to revive one meaningful thing from her past, finding a supportive and loving community of lost souls who become a multigenerational family-by-choice.